Paraneoplastic syndromes associated with gynecological cancers: A systematic review - Viau, Mathieu; Renaud, Marie-Claude; Grégoire, Jean; Sebastianelli, Alexandra; Plante, Marie (Gynecologic oncology, 2017)
•A variety of paraneoplastic syndromes can be associated with gynecological cancers.•These syndromes can affect all systems, and may lead to severe complications.•A systematic literature search identified those related to gynecologic oncology.•This article provides a summary and up-to-date information about each syndrome. A number of paraneoplastic syndromes have been described with gynecological cancers. These syndromes are induced by substances secreted by the tumor or by an immune response triggered by the cancer. Each system of the human body can be affected by different syndromes. Indeed, paraneoplastic syndromes occurring from tumors of the gynecologic tract were found to involve the nervous, ophthalmologic, dermatologic, rheumatologic, endocrine, hematologic and renal systems. These syndromes can manifest before, at the time, or after the diagnosis of cancer. They can also occur at the time of a recurrence. Knowledge about these syndromes is important for physicians caring for patients with cancers, as they can result in severe morbidity and must be treated appropriately. Literature regarding paraneoplastic syndromes associated with tumors of the female genital tract is scattered and the subject has not been reviewed recently. A systematic literature search was thus conducted to identify paraneoplastic syndromes associated with gynecologic cancers. This review focuses on the cancers involved with each paraneoplastic syndrome, and on their pathophysiology, clinical manifestations, possible complications, outcomes, and treatments. As the mainstay of treatment in these conditions is often to address the underlying tumor, it is of upmost importance that physicians be aware of these rare cancer manifestations.